Sex-specific foraging strategies and resource partitioning in the southern elephant seal (Mirounga leonina ) - Lewis, Rebecca (2006)
The evolution of resource specializations is poorly understood, especially in marine systems. The southern elephant seal (Mirounga leonina) is the largest of the phocid seals, sexually dimorphic, and thought to prey predominantly on fish and squid.We collected vibrissae from male and female southern elephant seals, and assessed stable C and N isotope ratios along the length of the vibrissae. Given that whiskers grow slowly, this sampling strategy reflects any variation in feeding behaviour over a period of time. We found that isotopic variation among females was relatively small, and that the apparent prey choice and trophic level of females was different from that for males. Further, males showed a very broad range of trophic/prey choice positions, grouped into several clusters, and this included isotopic values too low to match a broad range of potential fish and cephalopod prey tested. One of these clusters overlapped with data for South American sea lions (Otaria flavescens), which were measured for comparison. Both male southern elephant seals and southern sea lions forage over the continental shelf, providing the potential for competition.We discuss the possibility that individual southern elephant seals are pursuing specialist foraging strategies to avoid competition, both with one another, and with the South American sea lions that breed nearby.Mirounga leonina) is the largest of the phocid seals, sexually dimorphic, and thought to prey predominantly on fish and squid.We collected vibrissae from male and female southern elephant seals, and assessed stable C and N isotope ratios along the length of the vibrissae. Given that whiskers grow slowly, this sampling strategy reflects any variation in feeding behaviour over a period of time. We found that isotopic variation among females was relatively small, and that the apparent prey choice and trophic level of females was different from that for males. Further, males showed a very broad range of trophic/prey choice positions, grouped into several clusters, and this included isotopic values too low to match a broad range of potential fish and cephalopod prey tested. One of these clusters overlapped with data for South American sea lions (Otaria flavescens), which were measured for comparison. Both male southern elephant seals and southern sea lions forage over the continental shelf, providing the potential for competition.We discuss the possibility that individual southern elephant seals are pursuing specialist foraging strategies to avoid competition, both with one another, and with the South American sea lions that breed nearby.